Mapping Residential Land Suitability Using a WEB-GIS-Based Multi-Criteria Spatial Analysis Approach: Integration of AHP and WPM Methods - Anik Vega Vitianingsih; Ullum, Choirul; Maukar, Anastasia Lidya; Yasin, Verdi; Wati, Seftin Fitri Ana (Ikatan Ahli Informatika Indonesia (IAII), 2024)
Along with the increase in population and the acceleration of economic expansion, there has been a concomitant increase in the urgent requirement for additional property that can serve as a venue for a wide variety of community activities. It is not uncommon for large cities, which are the epicenter of urbanization, such as the city of Surabaya, to experience a sharp increase in the demand for land. One of the regions that has excellent accessibility is the Sidoarjo Regency, which is comparable to the City of Surabaya in this regard. The goal of this research is to use Web-GIS to conduct an analysis of spatial data to identify the land functions that are most suitable for use in residential areas. The Analytic Hierarchy Process (AHP) and the Weighted Product Model (WPM) are two of the methodologies that are included in the spatial data modeling method that uses multi-criteria decision making (MCDM). The parameters of the characteristics that are used are derived from data such as the distance to the city center, the distance to the market, the distance to the hospital, the distance to public transportation, the slope, the type of soil, and the amount of rainfall. The results of the spatial data modeling categorize the suitability of new residential land into categories of land that is not suitable for residential use and land that is acceptable for residential use. A K value of 0.27 is the result of the comparison test that was run between the two MCDM approaches using Cohen's Kappa coefficients.